Which pelvic ring fractures are potentially lethal?. Issue 6 (June 2015) - Ruatti, S.; Guillot, S.; Brun, J.; Thony, F.; Bouzat, P.; Payen, J.F.; Tonetti, J.
Abstract: Purpose: Global mortality of polytraumatised patients presenting pelvic ring fractures remains high (330%), despite improvements in treatment algorithms in Level I Trauma Centers. Many classifications have been developed in order to identify and analyse these pelvic ring lesions. However, it remains difficult to predict intra-pelvic haemorrhage. The aim of this study was to identify pelvic ring anatomical lesions associated with significant blood loss, susceptible to lead to life-threatening haemorrhage. Material and method: This study focused on a retrospective analysis of patients' medical files, all of whom were admitted to one of the shock rooms of Grenoble University Hospital, France, between January 2004 and December 2008. Treatment was given according to the institutional algorithm of the Alps Trauma Center and Emergency North Alpine Network Trauma System (TRENAU). Different hemodynamical parameters at arrival were measured, and the fractures were classified according to Young and Burgess, Tile, Letournel and Denis. One hundred and ninety seven patients were analysed. They were subdivided into two groups, embolised (Group E) and non-embolised (Group NE). Results: Group NE included 171 patients with a mean age of 40.2 ± 8.7 years (15–90). Group E included 26 patients with a mean age of 41.6 ± 5.3 years (18–67). Twenty-six patients died during the initial treatment phase. Eleven belonged to Group E and 15 to Group NE. Mortality was significantly higher in Group E (42.3% vs 8.8% in Group NE) ( p < 0.05). There were significantly many more Tile C unstable fractures in Group E ( p = 0.0014), and anterior lesions, according to Letournel, with pubic symphysis disruption were significantly more likely to lead to active bleeding treated by selective embolisation ( p = 0.0014). Posterior pelvic ring lesions with iliac wing fracture and transforaminal sacral fractures (Denis 2) were also more frequently associated with bleeding treated by embolisation ( p = 0.0088 and p = 0.0369 respectively). Discussion/conclusion: It appears that in our series the primary identification and classification of osteo-ligamentous lesions (according to Letournel and Denis' classifications) allows to anticipate the importance of bleeding and to adapt the management of patients accordingly, in order to quickly organise angiography with embolisation.